THE ROLE OF PROFESSIONAL TOURISM ASSOCIATIONS IN LATVIA - Vinklere, Daina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
After regaining independence in 1991, various sectors of the tourism industry in Latvia are united in professional associations. They represent various stakeholders of the industry in all processes important for tourism development and are part of the tourism management system of Latvia. So far, there has been no specific research conducted on the role of professional tourism organisations in Latvia. Therefore, the aim of this paper is to evaluate the achievements and future prospects of the activities performed by the national level professional tourism associations of Latvia. The empirical part of the research is based on the qualitative research methods – document analysis and structured interviews with board members and members of associations, as well as with a senior official at the Ministry of Economy of the Republic of Latvia. Research results reveal that the role of those organisations in Latvia is valuable and bring about a positive impact on the tourism industry. Despite the variety of opinions, the majority of interviewees believe that in the course of the next 5 years there will be an increasingly strong influence of associations on the development of tourism in Latvia.